Strategic Analysis Of Tools/Media Combination For Distance Learning In English Mathematic - Badriyah, Siti; Ningrum, Silvia; Qowiyyudin, Agus (Karimah Tauhid, 2024)
The distance learning process combines the principles of the learning process with technology. (Chandrawati, 2010), as well as a learning system that is used as a means for the teaching and learning process which is carried out without having to meet face to face between teachers and students (Ardiansyah, 2013). In e-learning, content is the most important thing that underlies the success of the learning process on internet media, apart from interaction content between users, it is also really needed as a substitute for the face-to-face process, content or teaching materials which on the internet can be in the form of text and presentations, but text content it is felt that it is still inadequate in meeting learning needs, another problem is that the content that is mostly used in the form of text or presentation slides has very minimal interaction so that some lessons, especially practical ones, will be more difficult to convey. The implementation of multimedia in distance learning will further improve the quality of e-learning because the problem with e-learning is that the content cannot explain the learning material because in general the content in e-learning only contains slides and material in PDF format which is less attractive.